Emestrin-type thiodiketopiperazines from Aspergillus nidulans SD-531, a fungus obtained from the deep-sea sediment of cold seep in the South China Sea. (May 2023) - Lv, Feng-Yi; Mándi, Attila; Li, Xiao-Ming; Chi, Lu-Ping; Li, Xin; Wang, Bin-Gui; Kurtán, Tibor; Meng, Ling-Hong
Abstract: Three new emestrin-type thiodiketopiperazines including didethio-11a-methylthioemestrin (1 ), 7′- epi -didethio-11a-methylthioemestrin (2 ), and 2″-desmethyl-MPC1001F (3 ), along with three known analogues emestrin (4 ), dethiosecoemestrin (5 ), and emestrin H (6 ), were isolated and identified from the culture extract of Aspergillus nidulans SD-531, a fungus obtained from the deep-sea cold seep sediment sample collected from the South China Sea. Their structures and absolute configurations were determined by spectroscopic analysis and TDDFT-ECD calculations. Compounds 3 –6 showed antimicrobial activity against some of the tested strains, while compounds 3 –5 had cytotoxic activity against the tumor cell line Huh 7.5. Compound 4 exhibited the strongest cytotoxic activity with an IC50 value of 0.25 μM, which was better than that of the positive control sorafenib. Graphical abstract: Image 1 Highlights: Secondary metabolites of the deep-sea-derived Aspergillus nidulans were studied. Three new and three known emestrin-type thiodiketopiperazines were characterized. Emestrin, a diketopiperazine with disulfide bridge, showed potent cytotoxicity.